Risk Factors of Non-en Bloc Resection and Non-R0 Resection During Endoscopic Resection in the Treatment of Superficial Duodenal Epithelial Lesions - Fu, Shifeng; Gong, Jian; Zhou, Mei; Wang, Yongjun; Liu, Deliang; Tan, Yuyong (Frontiers in Oncology, 2022)
Background: Superficial duodenal epithelial lesions are precancerous lesions of duodenal carcinoma. Upper gastrointestinal endoscopy has been widely used in the screening and treatment of this disease. This article will collect the data of patients who underwent endoscopic resection of superficial duodenal epithelial lesions in our hospital from 2010 to 2021, aiming to describe the efficacy and safety of endoscopic resection, as well as to explore the risk factors of non-en bloc resection and non-R0 resection. Methods: Patients who underwent endoscopic resection for superficial duodenal epithelial lesions in our hospital from January 2010 to September 2021 were selected. The curative effect was expressed by the en bloc resection rate and R0 resection rate. The safety was expressed by intra- or postoperative complications, such as bleeding and perforation. The potential risk factors of curative effect were analyzed by logistic regression. Results: A total of 137 patients were included. The en bloc resection rate was 95.62% (131/137), R0 resection rate was 91.97% (126/137), the postoperative bleeding rate was 2.19% (3/137), and no postoperative perforation was found. The histology result of ectopic gastric mucosa was the risk factor of non-en bloc resection (OR: 8.86, 95% CI: 1.38-56.92); the lesion size ≥2 cm was the risk factor of non-R0 resection (OR: 12.55, 95% CI: 2.95-53.38). Conclusion: Endoscopic resection is a safe and effective method for the treatment of superficial duodenal epithelial lesions. The histology result of ectopic gastric mucosa was the risk factor of non-en bloc resection and the lesion size ≥2 cm was the risk factor of non-R0 resection.